2015
DOI: 10.5009/gnl14206
|View full text |Cite
|
Sign up to set email alerts
|

Ampullary Adenoma Treated by Endoscopic Double-Snare Retracting Papillectomy

Abstract: We report herein improved methods for the safe and successful completion of endoscopic papillectomy (EP). Between January 2008 and November 2011, 12 patients underwent double-snare retracting papillectomy for the treatment of lesions of the major duodenal papilla. The main outcomes were en bloc resection rates, pathological findings, and adverse events. All of the patients (mean age, 60.1 years; range, 38 to 80 years) were diagnosed with ampullary adenoma by endoscopic forceps biopsies prior to endoscopic snar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Of these, 29 articles matched the selection criteria and were finally included in the analysis. 1241 Study characteristics and quality are comprehensively reported in Appendix 3. The baseline characteristics of the 1751 included patients are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 29 articles matched the selection criteria and were finally included in the analysis. 1241 Study characteristics and quality are comprehensively reported in Appendix 3. The baseline characteristics of the 1751 included patients are provided in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the title and abstract, 38 articles were retrieved as full text. Of these, 29 articles matched the selection criteria and were finally included in the analysis 12–41 . Study characteristics and quality are comprehensively reported in Appendix 3.…”
Section: Resultsmentioning
confidence: 99%
“…The technique was endoscopic double-snare for all 12 patients. The ampullectomy of these patients was safe and complete ( 9 - 11 ).…”
Section: Discussionmentioning
confidence: 89%
“…However, the results of the new trials have limitations due to the small number of patients. The different guidelines for various lesions were applied in eligible studies, and the therapeutic effects of ER and SR can be variable according to the reports [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In the current study, the overall information for the therapeutic effect and complication of ER was obtained through a meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Although surgical resection (SR) can have the possibility of complete resection, SR has higher morbidity and mortality compared to endoscopic resection (ER) [ 6 , 7 ]. In previous studies, ER showed a wide range of complete resection from 9.1% to 98.4% [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. The various factors can impact on variable rates.…”
Section: Introductionmentioning
confidence: 99%